Pengaruh Aplikasi LuvLingua Terhadap Penguasaan Goi Siswa SMA - Jihaan Nabiilah Bardan; Nova Yulia (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2025)
This research is motivated by the problems faced by students when studying goi, known because of the number of goi that must be memorized from each chapter This research aims to describe the influence of the LuvLingua application on the mastery of goi students in grade XI.F.10. This study uses a comparative method. The results of this study showed that the average value before using the LuvLingua application = 58 and after using the LuvLingua application = 85. The results of the Wilcoxon test show that the value of sig (2 tailed) = 0.000/2 < 0.05 until H0 is accepted H1 is subtracted. Based on these results, it can be concluded that the LuvLingua application has an effect on the mastery of goi at a significance level of 0.05.